Analysis of the hemostatic efficacy of polyurethane foam using a novel method to compare topical hemostatic agents in a rat tail-tip model - Broekema, Ferdinand I.; Oeveren, Wim Van; Bos, Rudolf R.M. (International Surgery Journal, 2016)
Background:A broad variety of topical hemostatic agents are used in the surgical disciplines. We analysed the most widely used topical hemostatic agents and compared them to a recently developed, synthetic topical hemostatic agent based on polyurethane (PU). The materials were compared using a novel testing method based on a rat tail-tip model. Tests were also performed with PU that was enriched with the procoagulant substance chitosan to evaluate if this could increase its hemostatic efficacy. Methods: The following topical hemostatic agents were compared using a rat tail tip model: Collagen, gelatin, oxidized regenerated cellulose, chitosan dressing, PU and PU with chitosan. The tail tip was fixated on a developed test device to ensure a constant and equal pressure of the test material on the wound. The mean bleeding time was determined and compared between the groups. Results:PU showed a mean bleeding time of 23.9 min. This was not significantly shorter or longer than gelatin (23.6 min), collagen (28.2 min) or oxidized regenerated cellulose (26.9 min). The addition of chitosan to PU did lead to the shortest mean bleeding time (21.5 min) but this was not significantly faster than PU without chitosan. Conclusions:These results show that PU is a promising alternative for the most widely used topical hemostatic agents. Future studies will have to show if the addition of procoagulant substances like chitosan can significantly improve the hemostatic efficacy of PU.